(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Cervical myelopathy is a condition caused by narrowing of the spinal canal leading to cord dysfunction. The most common causes are congenital stenosis and degenerative stenosis caused by spondylosis. Objectives:To confirm the diagnosis of cervical myelopathies using somatosensory evoked potentials and possibly to localize the level of the lesion. Methods: An electrophysiological study had been carried on 61 patients with cervical myelopathy (41 female and 20 male) aged 48.66±11.72 years and 41 healthy volunteers aged 44.8±10.53 years. Sensory and motor nerve conduction study and somatosensory evoked potential for all were done to evaluate the peripheral nerves and sensory central pathways. Results:No significant difference was demonstrated in the sensory and motor nerve conduction studies from the healthy subjects. Somatosensory evoked potentials showed statistically highly significant changes in the N13, N20 latencies, amplitudes and N13-N9 and N20-N13 central sensory conduction times of median nerve on both sides. N13 latency has the highest specificity and sensitivity among the somatosensory evoked potentials parameters. Those patients who had prolonged central sensory conduction time between N20-N13 suggests an upper cervical lesion while those having prolonged central sensory conduction time between N13-N9 suggest lower cervical cord and/or cervical root affection. Conclusion:Motor and sensory conduction studies are usually normal in CM. Among SSEPs parameters, N13 latency was prolonged bilaterally, CSCT abnormal bilaterally, N13-N9 and N20-N13 latencies unilaterally (Right side). Mononeuropathies, polyneuropathies, radiculopathies and plexopathies should be excluded before diagnosis of CM was made. Key words:Cervical myelopathy, electroneuromyograhpy, somatosensory evoked potentials.